Pozzolanic activity of tiles, bricks and ceramic sanitary-ware in eco-friendly Portland blended cements. (10th January 2021) - Pitarch, A.M.; Reig, L.; Tomás, A.E.; Forcada, G.; Soriano, L.; Borrachero, M.V.; Payá, J.; Monzó, J.M.
Abstract: Reusing ceramic waste as a pozzolanic admixture may offer environmental benefits as it allows the reduction in the consumption of natural resources and energy, and the reduction of CO2 emissions associated with Portland cement (PC) production, while valorising waste materials with a long biodegradation period. This paper assessed the pozzolanic activity of three different ceramic waste types: red clay bricks (RCB), ceramic tiles (TCW) and ceramic sanitary-ware (CSW). After adapting their particle size by crushing and milling, each was used to replace 0 to 50 wt% PC (CEM I 42.5 R type). The milled powders were characterised by laser diffraction, field emission scanning electron microscopy (FESEM), X-ray fluorescence (XRF) and X-ray diffraction (XRD), and consistency and setting time tests were used to investigate the fresh behaviour of the ceramic waste/PC blended pastes. A basic sustainability analysis was performed, and the pozzolanic activity of RCB, TCW and CSW was assessed by compressive strength tests (performed in mortars cured at room temperature from 3 to 365 days) and microstructural analyses (thermogravimetry, XRD and FESEM performed in the pastes cured at 20 °C for 28 and 90 days). The pozzolanic reaction of these waste materials improved with curing time, and all the mortars prepared with up to 25 wt% RCB, TCW or CSW met the mechanical requirements set out for coal fly ashes, whatever the ceramic waste type used. Among them, these results open up the possibility of partially replacing PC with the closest available ceramic waste, which would reduce the CO2 emissions and economic cost deriving from transporting waste. Graphical abstract: Image 1 Highlights: PC may be replaced with up to 25% RCB, TCW or CSW ceramic waste materials. Similar strength results were obtained after 365 days for a given amount of waste. RCB exhibited slightly better pozzolanic activity for short curing ages. Consistency increased with RCB, diminished with CSW and hardly varied with TCW. RCB and TCW slightly cut and CSW somewhat prolonged the final setting time.